Subjective mental fatigue ratings are not associated with basketball game-related statistics during official semiprofessional male games - Sansone, Pierpaolo; Fortes, Leonardo de Sousa; Polverari, Damiano; Leicht, Anthony; Gomez-Ruano, Miguel Angel (Frontiers in Psychology, 2025)
IntroductionMental fatigue (MF) has been shown to affect several domains of team sports performance, including physical, technical, and perceptual-cognitive aspects. This study examined whether subjective ratings of mental fatigue (MF) are associated with technical-tactical performance in adult male basketball official games.MethodsFourteen semiprofessional players (age: 22.1 ± 3.8 years) were monitored across 15 in-season weeks, encompassing 17 official games. The day before the game, players reported their level of MF using 100-mm visual analog scales. Technical-tactical performance during games was assessed by retrieving game-related statistics (GRS) (points; 2-point shots (2P) made; 2P missed; 2P percentage (2P%); 3-point (3P) shots made; 3P shots missed; 3P shot percentage (3P%); free-throws (1P) made; 1P missed; 1P percentage (1P%); offensive rebounds; defensive rebounds; assists; steals; turnovers; blocks; blocks against; fouls committed; fouls drawn; and Performance Index Rating). To control for games with different paces, games were coded as faster or slower according to the number of ball possessions. Separate linear mixed models evaluated the effects of variations in MF (z-scores) on GRS.ResultsMF did not influence any GRS (all p > 0.05), while 3P misses were higher in faster games compared to slower (p = 0.049).ConclusionsSubjective ratings of MF are not associated with technical-tactical performance in male semiprofessional basketball. Current findings indicate that male semiprofessional basketball players are able to maintain technical-tactical performances despite the presence of MF.